Feasibility Assessment of Nampu Leaf Processing Bussines: a Case Study in The Mount Sawal Area - Suhartono; Endah Suhaendah; Eva Fauziyah; Aris Sudomo; Levina Augusta Geraldine (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
Dried nampu leaves have become an export commodity as raw materials for the pharmaceutical, cosmetic, and herbal cigarette industries. However, the massive exploitation of nampu leaves in their natural habitat in forest areas has raised concerns that it could disrupt forest sustainability. Therefore, financial analysis is needed to find out whether this business could be expanded or not. This study aims to examine the feasibility of processing nampu leaves into dried chopped leaves, the challenges and the prospects for its development. We conducted a case study on a nampu leaf processing business group in Cihaurbeuti Subdistrict, Ciamis, West Java. Data was collected through in-depth interviews and field observations. The results showed that the nampu leaf processing business was feasible because of the availability of resources, an easy process and a relatively short payback period as indicated by the R/C value of 1.17 and BEP production of 2,596.15 kg and BEP sales of IDR38,942,307 which can be achieved in less than 1 year. The challenges of this business are the availability of raw materials, marketing guarantees and forest sustainability. Government assistance is very important in supporting the sustainability of this business.